Effects of Field Trip on Academic Performance and Retention in Ecology Concept among Senior Secondary School Students in Akko LGA, Gombe State, Nigeria - Yer , Chinkinan John; Ibrahim, Ahmed; Yilshik, Obed Musa (Kashere Journal of Education, 2025)
The study investigated the effects of field-trip on academic performance and retention in ecology concept among senior secondary school students in Akko Local Government Area, Gombe State. The objectives of the study were to examine the effects of field trip on Biology students’ academic performance and retention in senior secondary schools. Two research questions and two corresponding hypotheses were formulated and tested at 0.05 level of significance. A quasi-experimental design which utilized pre-test post-test non-control group design was adopted. The population of the study consisted of all the 2,487 SS2 students from twenty-six (26) public schools in Akko Local Government Area Gombe State. A simple random sampling technique was employed to select a sample of 205 students from two intact classes drawn from two schools out of the 26 secondary schools in the study area. One school served as experimental group and the other school as control group. One instrument titled “Biology Achievement Test (BAT)” was used for data collection. The BAT was validated by experts after which the split half method was used to establish the reliability of the instrument using Pearson Product Moment Coefficient and a reliability of 0.847 was obtained Research questions were answered using descriptive statistics of mean and standard deviation, while the hypotheses were tested using inferential statistic of independent sample t-test. The findings of study revealed that field trip teaching strategy has significant positive effects on students’ performance as it enhanced the performance of students in Ecology. It also concluded that field trip teaching strategy enhances students’ retention of ecological concepts. The study recommended among others that Biology teachers should employ field trip strategy and activities to augment the conventional lecture method being used by many teachers in Nigeria. Also, the Ministries of Education should impress on school principals to ensure that teachers employ the use of field trip teaching strategy particularly in the teaching and learning of ecology concept at senior secondary school level.